2015
DOI: 10.1155/2015/265798
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain Modulates Zymosan‐Induced Peritonitis in Mice

Abstract: Ouabain, a potent inhibitor of the Na+, K+-ATPase, was identified as an endogenous substance. Recently, ouabain was shown to affect various immunological processes. We have previously demonstrated the ability of ouabain to modulate inflammation, but little is known about the mechanisms involved. Thus, the aim of the present work is to evaluate the immune modulatory role of ouabain on zymosan-induced peritonitis in mice. Our results show that ouabain decreased plasma exudation (33%). After induction of inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
44
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 51 publications
10
44
1
2
Order By: Relevance
“…Moreover, ouabain exhibited nociceptive actions in the acetic acid-induced writhing response and in the hot plate model. These findings were corroborated and expanded in a study by Leite et al [33], who showed that ouabain (560 µg/kg bodyweight) decreased zymosan-induced peritonitis in mice. The compound reduced fluid extravasation (edema formation), leukocyte infiltration and the levels of the cytokines IL-1β and tumor necrosis factor α (TNFα), but did not influence the viability or function (phagocytosis) of leukocytes.…”
Section: Acute Inflammationsupporting
confidence: 76%
“…Moreover, ouabain exhibited nociceptive actions in the acetic acid-induced writhing response and in the hot plate model. These findings were corroborated and expanded in a study by Leite et al [33], who showed that ouabain (560 µg/kg bodyweight) decreased zymosan-induced peritonitis in mice. The compound reduced fluid extravasation (edema formation), leukocyte infiltration and the levels of the cytokines IL-1β and tumor necrosis factor α (TNFα), but did not influence the viability or function (phagocytosis) of leukocytes.…”
Section: Acute Inflammationsupporting
confidence: 76%
“…Numerous studies have shown CTS, as natural ligands of NKA, to have modulatory effects on immune cells functioning in vitro and in vivo ( 9 11 , 13 , 14 ).…”
Section: Cardiotonic Steroids the Specific Ligands Of Nkamentioning
confidence: 99%
“…Numerous studies have shown CTS to modulate the function of many immune cells, both in vitro and in vivo , with effects via the inhibition of NF-κB and MAPK, thereby controlling some key cellular processes, such as proliferation and differentiation, as well as cytokine production ( 9 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zymosan, a polysaccharide cell wall component derived from Saccharomyces cerevisiae, is commonly used for the induction of peritonitis and can lead to inflammation [44]. Therefore, it has been widely used as a self-resolving model of inflammation within 30 min of the inflammatory stimulus due to the activation of macrophages and mast cells that release prostaglandins, particularly histamine and leukotrienes [45]. In this study, we used the acetic acid-induced vascular permeability model and zymosan-induced peritonitis model extensively to study the effects of o-VA. Our data demonstrated that o-VA could suppress the migration of leukocyte by inhibiting capillary permeability.…”
Section: Discussionmentioning
confidence: 99%